Impact of internal migration on political participation in turkey - Ali T. Akarca; Aysit Tansel (IZA Journal of Migration, 2015)
The Impact of population mobility on provincial turnout rates in the 2011 Turkish parliamentary election is studied, controlling for the effects of other socio-economic, demographic, political and institutional factors. Consequences of migration both at destinations and origins are considered. According to the robust regressions estimated, the relationship between turnout and education is inverse U-shaped, and between turnout and age (including generational effects), it is U-shaped. Immigration, emigration, large population, a large number of parliament members elected from a constituency, participation by large number of parties, and existence of a dominant party depress the turnout rate. However, at destinations where large numbers of immigrants from different regions are concentrated, the opportunity afforded to them to elect one of their own reduces the adverse impact of immigration significantly and in some cases even turns it to positive. That emigration, and education beyond certain level, have negative effects on turnout, that immigration's adverse effect is less in areas with high migrant concentrations, and that in Turkey, political participation is highest among the youngest voters are the novel findings of the study. The latter finding may explain why voter turnout declines in Europe and North America but not in Turkey.
Keywords: D72; J61; 330; Election; Turnout; Voter behavior; Political participation; Internal migration; Turkey